2020
DOI: 10.1007/s43452-020-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic behavior of strong beam–weak column joints strengthened with different configurations of CFRP sheets

Abstract: The current paper reports the results of experiments on deficient exterior reinforced concrete (RC) strong beam-weak column connections strengthened with carbon fiber-reinforced polymer (CFRP) sheets. Five RC-joint specimens with half-scale size were manufactured and tested subjected to constant axial and reversed cyclic quasi-static loads. These joints consisted of one control and four specimens retrofitted with FRP sheets used in different strengthening configuration. The study is mainly directed to the exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The strengthening of concrete structures is the field of construction where composite materials made of FRPs (fibrereinforced polymers) are being introduced most quickly and with the greatest success [1,2], mainly due to their corrosion resistance, good mechanical properties and lightness that translates into ease and savings in the execution of works. Typical FRP applications include flexural strengthening [3], shear strengthening [4] or strengthening of beam-column joints suffering from both flexural and shear deficiencies [5].…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of concrete structures is the field of construction where composite materials made of FRPs (fibrereinforced polymers) are being introduced most quickly and with the greatest success [1,2], mainly due to their corrosion resistance, good mechanical properties and lightness that translates into ease and savings in the execution of works. Typical FRP applications include flexural strengthening [3], shear strengthening [4] or strengthening of beam-column joints suffering from both flexural and shear deficiencies [5].…”
Section: Introductionmentioning
confidence: 99%
“…The test concluded that the EBROG technique combined with the FRP anchors has successfully eradicated the debonding failure of the FRP composites and enhanced the seismic capacity of the BCJ. A similar study was conducted by Ilia et al [47] using the EBROG technique in combination with FRP anchors in the X-shaped layout to strengthen the deficient BCJ. It was concluded that the EBROG technique along with other combinations successfully eliminated the debonding of the FRP composites and improved the strength characteristics of the weak column-strong beam joints.…”
Section: Introductionmentioning
confidence: 81%
“…To assess the effectiveness of L-shaped CFRP sheets (LCS), only the BCJ of the ground floor slab was strengthened with LCS. To avoid debonding of the FRP composites, which is most likely to occur at the beam-column interface [24,47], a narrow opening in the slab adjacent to the beam along with complete wrapping around the L-shaped FRP sheets were proposed. The ACI 440.2R also suggests the superior performance of a complete wrapping around the perimeter of the strengthened section [51].…”
Section: Preliminary Design Of Frp Composite Retrofit Schemementioning
confidence: 99%
“…In this paper, all previous studies using the grooving method to retrofit structural members were evaluated. A total of 445 tests were performed by these studies, out of which 141 tests were for flexural strengthening of beams and slabs [44][45][67][68][69][70][71][72][73][74][75][76][77][78][79][80], 86 tests for shear strengthening of beams [81][82][83][84][85][86][87][88], 182 tests for strengthening columns [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], and 36 tests for strengthening beam-column joints [106][107][108][109][110][111][1...…”
Section: Introductionmentioning
confidence: 99%